Intellectual Property Rights (IPR) Issues for Libraries in the Era of Digital Preservation and Dissemination of Information - Pandey, Satya Nand (Journal of Information and Knowledge, 2015)
Digital Libraries have been proved as a boon for the library users and the present era has created a platform for the libraries from where information can be disseminated through a wider service network. But some how these are quite threatened by Intellectual Property Right infringement issues. Information which is selectively acquired by libraries but can be easily transferred to some other platform must be protected. In this paper Intellectual Property Rights related to libraries have been discussed.